Determining Seismicity Using the Likelihood Method in Sumbawa Island Region Period 1972-2022 - Celline; Winardi Tjahyo Baskoro; Muhammad Soekarno Saputra Rahman (Kappa Journal, 2024)
Research has been carried out regarding the determination of seismicity in the Sumbawa Island region for the period 1972-2022 with observation area boundaries of 116.5° – 119.3° East Longitude and 10° – 8° South Latitude. The research was carried out at the Center for Meteorology, Climatology and Geophysics Region III Denpasar using the likelihood method which was adjusted to the seismicity level M ≥ 3 and depth ≤ 30 km. Determining the b-value was calculated using the likelihood method and obtained b-values for the 4 regions ranging from 0.6 – 0.7 and a-values ranging from 4.7 – 5.4. The return period for earthquakes ranges from 1.03 – 308.1 years. The results show that region 3 has the largest b-value, namely 0.796. The region that has the largest a-value is region 1, namely 5.405. The shortest earthquake return period is region 1 with 1.049 years and the longest is region 3 with 314.6 years.